Isolated Peritoneal Metastasis Creating Confusion in Carcinoma Cervix – a Case Report and Review of Literature - Dr. Gunjesh Kumar Singh (International Journal of Allied Medical Sciences and Clinical Research, 2020)
Carcinoma cervix commonly spreads locally and through lymphatic channels. Peritoneal metastasis (PM) is an extremely rare entity. We present a case of a 35-years-old female with carcinoma cervix, who presented with bleeding per vaginum along with pelvic pain and posed diagnostic confusion on contrast enhanced computed tomography (CECT). To the best of our knowledge, till date only two similar cases of carcinoma cervix with PM have been reported in the literature.